Applying of Techniques of Technology for the Development of Critical Thinking Through Reading and Writing When Learning Russian as a Non-Native Language (Eurasian Research Bulletin, 2022)
The article highlights the use of innovative methods of Technology for the development of critical thinking through reading and writing when teaching Russian as a non-native language on the example of such techniques as Cluster, Search for correspondences, Ranking. The universality and effectiveness of the application of these techniques at all stages of the lesson are considered.